CYP51A1 in health and disease: from sterol metabolism to regulated cell death - Fangquan Chen; RuiRui Liang; Jieting Zhang; Rui Kang; Daolin Tang; Jiao Liu (Cell Death Discovery)
Abstract How do cells precisely coordinate sterol metabolism with survival and death signals in diverse physiological and pathological contexts? This fundamental question has gained increasing attention as accumulating evidence reveals that enzymes traditionally associated with lipid biosynthesis may have unexpected regulatory functions beyond metabolism. Cytochrome P450 family 51 subfamily A member 1 (CYP51A1), a conserved sterol 14α-demethylase essential for cholesterol synthesis, exemplifies this emerging concept. Although well-characterized as an antifungal drug target in microorganisms, the roles of human CYP51A1 in development, cell death regulation, and disease pathogenesis remain underexplored. Recent studies have uncovered that CYP51A1 not only contributes to cholesterol homeostasis but also modulates multiple forms of regulated cell death—including apoptosis, ferroptosis, alkaliptosis, and pyroptosis—via sterol intermediates or cholesterol-independent mechanisms. Moreover, dysregulation of CYP51A1 has been implicated in a wide spectrum of diseases, such as cancer, cataracts, Antley-Bixler syndrome, autoimmune disorders, metabolic liver disease and neurodegeneration. In this review, we provide a comprehensive synthesis of CYP51A1’s structure, regulatory networks, and non-canonical functions. We propose a unifying framework in which CYP51A1 integrates metabolic reprogramming and cell fate control, highlighting its potential as a therapeutic target across diverse human diseases.